The Recovery of State Assets Due to Bankruptcy in State-owned Enterprises - Gusti Ayu Ketut Rachmi Handayani, I; Anwar, Kairul; ., Hartiwiningsih; Jaelani, Abdul Kadir (KnE Social Sciences, 2024)
This research intended to examine the elements of state loss on Indonesian corruption regulations and to assess the effort of asset recovery concerning state loss, resulting from corruption based on Indonesian law. This was normative legal research employing the statutory approach, the conceptual approach, the fact approach, and the case approach. The study revealed that the components of state loss consist of actual shortages of cash, securities, and goods; it was caused by illicit actions, either intentionally or negligently; and losses whose amount can be calculated based on the findings of the authorized agency or appointed public accountant. In the Indonesian legal system, asset recovery initiatives can be analyzed through the lens of both criminal and administrative laws. According to criminal law, asset recovery can occur in multiple stages of the criminal justice system, whereas under administrative law, asset recovery must comply with Article 34 of Government Regulation No. 48 of 2016 on the procedures for imposing administrative sanctions on government officials. Keywords: bankruptcy, state assets, state-owned enterprises